Diagnostic and predictive value of Respiratory Index of Severity in Children (RISC) scoring system in community-acquired pneumonia: a prospective cross sectional study - Mohamed Abdallah Abd El Megied; Mohammad Abdel Fattah Abdel Motey; Miriam Magdy Aziz; Mohammed Mohammedy Ebrahim (SpringerOpen, 2023)
Abstract Background Community-acquired pneumonia (CAP) exhibits high mortality rates among children, accounting for up to 50% in severe cases. Respiratory Index of Severity in Children (RISC) score is a six-predictor standardized means for assessment of the severity of respiratory illness among children. The aim of this study was to validate the RISC score in evaluation of mortality outcome in hospitalized infants diagnosed with CAP. Methods This prospective cross-sectional study was conducted on 150 Egyptian children who were diagnosed to have CAP, admitted to the general wards and pediatric intensive care units (PICUs) of Cairo University Children Hospital, Faculty of Medicine, Cairo University from September 2019 to June 2020. Results Median RISC score was significantly higher in non-survivors compared with survivors (p < 0.001). There were significant direct correlations between RISC score and each of respiratory distress grade, C-reactive protein (CRP), PICU admission, mechanical ventilation (MV) and mortality (p < 0.05). The RISC score, assessed within 24 h of admission, had sensitivity of 85.71%, and specificity 89.51% in discriminating infants with CAP who survived from those who died (determined at a cut off > 3). The RISC score was a significant predictor for mortality in infants with CAP (Odds ratio = 5.17, p < 0.001). Conclusion The RISC score helps in prediction of mortality among children with CAP. Future studies are needed to validate RISC score as a guide for effective management protocol.